2022
DOI: 10.3390/cancers14174168
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70–Bag3 Module Regulates Macrophage Motility and Tumor Infiltration via Transcription Factor LITAF and CSF1

Abstract: The molecular chaperone Hsp70 has been implicated in multiple stages of cancer development. In these processes, a co-chaperone Bag3 links Hsp70 with signaling pathways that control cancer development. Recently, we showed that besides affecting cancer cells, Hsp70 can also regulate the motility of macrophages and their tumor infiltration. However, the mechanisms of these effects have not been explored. Here, we demonstrated that the Hsp70-bound co-chaperone Bag3 associates with a transcription factor LITAF that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…In this context, the results of the present study showing lysosomal degradation of CDIP1 provide supporting evidence that CDIP1 is a membrane-integrated protein. On the other hand, for LITAF, a paralog of CDIP1, some reported data indicate that it is degraded mainly by lysosomes [ 16 ], while other data suggest that both the lysosomal and proteasomal pathways are involved in its degradation [ 48 ]. Differences in degradation pathways may reflect differences in the membrane-localized proportions of LITAF proteins or may result from differences in experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the results of the present study showing lysosomal degradation of CDIP1 provide supporting evidence that CDIP1 is a membrane-integrated protein. On the other hand, for LITAF, a paralog of CDIP1, some reported data indicate that it is degraded mainly by lysosomes [ 16 ], while other data suggest that both the lysosomal and proteasomal pathways are involved in its degradation [ 48 ]. Differences in degradation pathways may reflect differences in the membrane-localized proportions of LITAF proteins or may result from differences in experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on BAG3 mostly focused on the correlation between BAG3 mutation and genetic diseases such as dilated cardiomyopathy [31][32][33]. With the incremental understanding on BAG3, its various roles as a molecular chaperone have been gradually discovered [34,35]. In addition, numerous studies have shown that BAG3 plays an indispensable role in autophagy and cell survival by bridging multiple signaling pathways [9,11,12,22].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still unclear how UBR5 affects p53, which may be related to UBR5‐mediated ubiquitination and degradation (Song, Yeku, et al, 2020). Avinery et al (2022) found that the Hsp70‐Bag3 complex inhibits TAMs migration and infiltration by reducing CSF‐1 through UPS degradation of highly expressed transcription factor lipopolysaccharide TNF‐α factor (LITAF) in TAMs. A recent analysis showed that the core component of SKP1 cullin 1‐Fbox E3 ubiquitin ligase, FBXO1 (CCNF), FBXO20 (LMO7), FBXO22, FBXO28, FBXO32, and FBXO45 were generally negatively associated with TAMs infiltration (Zhang et al, 2022).…”
Section: Effect Of the Ups On Tamsmentioning
confidence: 99%
“…In a study of triple-negative breast cancer (TNBC), COP1 E3 was shown to bind to C/EBPδ via the linker protein Trib2 and to mediate the ubiquitinated degradation of C/EBPδ via UPS (Wang et al, 2021). C/EBPδ, a member of the CCAAT/enhancer binding protein (C/EBP) transcription factor family, acts as a tumor suppressor that not only induces cancer cell growth arrest and apoptosis (Balamurugan & Sterneck, 2013) but also inhibits the transcription of macrophage chemokines released from cancer cells.…”
Section: Cop1 (Constitutive Photomorphogenic 1 Also Known As Rfwd2)mentioning
confidence: 99%